Automating Morals – On the Morality of Automation Technology, Ironies of Automation and Responsible Research and Innovation. Issue 2 (2020) - Herzog, Christian; Hoffmann, né
Abstract: The prevalence and impact of morals in technology design is increasingly better understood. Likewise, advances in machine learning, systems theory and control continue to push the boundary with respect to the applications in which automation may be considered. The present paper is intended to act as a precursor to a lively debate about professional ethics within the control community regarding automation in morally charged situations and beyond. First, the paper provides a primer on the actualities of applications in which morals already play a significant role. It further claims that–in contrast to typical expositions–within the scope of systems in which automation is employed, there is a continuum between addressing morally charged contexts to actually performing a kind of automated moral deliberation, though technically and philosophically there may be a vast difference. Second, from this perspective, the paper presents a first indication about potential new and persistent "ironies" within the context of automating morals. Third, the paper draws conclusions, essentially calling for the community to open up and engaging in participatory research and development settings as a matter of professional ethics.